Blockchains and the token economy : theory and practice - Lacity, Mary Cecelia; Treiblmaier, Horst (Technology, work and globalization., 2022)
In the context of blockchain technologies, tokens present a novel way to transfer value between parties without relying on traditional intermediaries. The so-called token economy has only recently attracted the attention of practitioners and academics, who seek to understand the potential of tokenization, but also its challenges and pitfalls. In this book, leading practitioners and academics provide a comprehensive overview explore theories on the future of the token economy and provide real world case studies from a range of industries. Chapter 3 and Chapter 8 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com. Mary C. Lacity is Walton Professor of Information Systems and Director of the Blockchain Center of Excellence in the Sam M. Walton College of Business at The University of Arkansas, USA. Horst Treiblmaier is a Professor in International Management at Modul University Vienna, Austria.